ISLE-Based Learning Media Development Using PhET Simulation to Reduce Misconceptions on Parabola Motion Materials - Dian Rafika; Rajibussalim; Nasrullah Zaini; Yusrizal; Muhammad Syukri (Jurnal Penelitian Pendidikan IPA, 2023)
The objective of this study is to develop ISLE-based learning media using PhET Simulation to minimize students’ misconception about parabolic motion concept. This study employs research and development methods (Research and Development/R&D) with the ADDIE development model (Analysis, Design, Develop, Implement, and Evaluate). The results from this study are learning media in the form of ISLE-based Student Worksheets for parabolic motion experiments. To obtain credibility and validity results, the learning media has followed the validation process from material and media experts. Therefore, the learning media is suitable to be implemented for students. The results indicated that the feasibility of developed learning media student worksheet assists students to visualize parabolic motion. Student worksheet prepared using the ISLE model approach is used as a guide in achieving learning objectives to reduce students' misconceptions about parabolic motion concept through PhET Simulations. Moreover, the use of learning media student worksheet provides a visualization display of experimental results which helps students in understanding the concepts and there was a decrease in misconceptions in parabolic motion matter from 42.22 to 12.78%.